ASSESSMENT OF ENDODONTIC IRRIGANTS USED IN THE MANAGEMENT OF OPEN APEX CASES - A RETROSPECTIVE STUDY - Ranjan Pandey, Shree; S., Haripriya; K, Sowmya (International Journal of Psychosocial Rehabilitation, 2020)
Normal physiological root end closure plays a significant role in the development of the tooth. When this normal physiological root end closure does not occur, it leads to incomplete root end closure where the walls of radicular dentine are parallel to each other. In the field of endodontics, these cases are termed as open apex cases. Open apex cases are mostly having a history of trauma associated previously. Open apex cases are a challenge to deal with in the field of endodontics, as after trauma without the formation of a complete root or without the closure of the apical barrier, the infection caused due to pulpal necrosis. The following study deals with the association between the various kinds of endodontic irrigants used in the management of open apex cases. This university-based study involved the collection of data from the hospital-based records; 86000 patient case records were assessed. After analyzing the data of 43 patients who had undergone treatment, 55 open apex cases were analyzed. The data was compiled and tabulated in Microsoft Excel and exported to IBM SPSS 20. Data was represented through frequency distribution tables, and chi-square tests were performed to compare the various endodontic irrigants used for the management of open apex cases. The maximum number of open cases was reported in the age group of 11-20 years (48.84%). Prevalence of open apex was higher in males (63.72%). The maximum number of open apex cases are seen in 11 & 21 (74.55%), and the least is 36.46 (1.82%). Association between teeth with open apex and the irrigants used revealed that most commonly used irrigant was saline and there was no statistical significant difference between the types of irrigants used in the management of open apex cases